Pellet Formulation of Trichoderma Isolated from Aceh with Potential for Biocontrol of Phytophthora Sp. on Cacao Sedlings - Rina Sriwati; Tjut Chamzhurni; Alfizar Alfizar; Bonny PW Soekarno; Vina Maulidia; Irza Sahputra (Politeknik Pertanian Negeri Payakumbuh, 2019)
Molleculler study was conducted to identify several species of Trichoderma isolate from several plant (Pine, Cacao, Gliceria, Nutmeg, Bamboo, Coffee, Potato). The growth of eight species Trichodermaafter pelleting formulation has been observed. Pellet Trichoderma harzianum have good ability to growth on PDA medium after 4 weeks storage. Base on their mycelium diameter growth on PDA, T. harzianum have selected as potential species on pellet formulation growth. Several dose of pellet formulation have been applied for controlling Phythopthora disease. The application of T. harzianum pellets in the form of a 2 g / 100 ml (S1) suspension effective in inhibiting the development of Phytophthora sp in cacao seedlings, when the higher concentrations of T. harzianum pellets applied to cacao seeds,the disease severity increase. Pellet Trichoderma could be use as biological control agent of cacao seedling in certain dosage.